Study of Cooling Characteristics of Axisymmetric Tail Nozzle - Hao Zeng; Rui Xi; Yiwen Li; Xingyao Hou; Changqin Fu (Energies, 2024)
In order to reduce the infrared radiation intensity of supersonic tail nozzles and in response to the increasingly severe battlefield infrared environment, simulations were conducted on axisymmetric expanding tail nozzles to study the effects of air, liquid nitrogen, and dry ice cold flows at different flow rates on the nozzle wall temperature. The results show that when the dry ice flow rate is increased by 1 kg/s, the maximum temperature of the wall surface in the expansion section decreases by about 40 K. At a cold flow rate of 5% in the 0° detection direction, the intensity of infrared radiation was reduced by 20.8% for the liquid nitrogen cold flow and 26.3% for the dry ice cold flow, compared to the cold flow of injected air. The IR suppression of the tail nozzle was significant in the range from α = 0 to 50°. Compared to cooling air, the maximum IR radiation intensity was reduced by 26.5% for dry ice and 20.4% for liquid nitrogen. When the flow rate of the injected cold stream was increased by 4%, the intensity of the infrared radiation from the nozzle was reduced by 52.6%, 55.8%, and 66.2% for the injected air, liquid nitrogen, and dry ice cold streams, respectively.